Efektivitas Pemanfaatan Aplikasi Zoom Dalam Dakwah kyai Choirul Anam Terhadap Tingkat Pemahaman Agama Komunitas Santri Ta’dhim : Dakwah, Zoom Meeting, Pemahaman Agama - Harlina Nurfaisa, Nani; Islam, Ahmad Fakhruddin Fajrul (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
The rapid development of technology requires individuals to be able to utilize it effectively. Advanced technology, such as Zoom Meetings, enables individuals or groups to obtain information. The ease of access to information sometimes necessitates analysis to determine its truth or falsehood. In this context, Kyai Choirul Anam provides religious knowledge through preaching. The preaching is conducted not only offline but also online via Zoom Meetings, which can be attended by everyone. Students who participate in the religious study sessions via Zoom form a community called the Santri Ta’dhim community. In this study, the researcher aims to assess the level of religious understanding in the Santri Ta’dhim community using quantitative correlational analysis. Data collection involved 21 samples who were given a Google Form questionnaire. The significance value was rejected, indicating no effect on the level of religious understanding in the Santri Ta’dhim community, as the significance value was greater than 0.05. The correlational analysis assisted by SPSS 25 yielded a significance value of 0.425, meaning the alternative hypothesis (Ha) was rejected.